2019
DOI: 10.1021/acs.iecr.9b05534
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Structural, Electrochemical, and Electrode Kinetic Properties of Na0.5Ni0.2Mg0.1Mn0.7O2 Material for Sodium-Ion Battery Applications

Abstract: The hybrid P3/P2-structured Na 0.5 Ni 0.3 Mn 0.7 O 2 as a cathode material for sodium-ion batteries (SIBs) demonstrates high initial discharge capacity. However, the existence of an unstable P3 phase leads to a fast capacity fade that is adverse to engineering applications. Herein, the introduction of inactive magnesium to partially replace electrochemically active nickel of Na 0.5 Ni 0.3 Mn 0.7 O 2 is proposed to reinforce the structural stability of the material. It is found that magnesium incorporation can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Diffraction peaks of the four groups of samples matched well with the standard PDF card (PDF: #54-0894). 30 Four groups of samples belong to the hexagonal system, with the P63/mmc spatial group, indicating that these samples have a P2-type layered structure (Supporting Information Figure S1). The diffraction peak of the NiO impurity phase is observed in the doped samples, which is related to the dissolution limit of nickel ions in the P2 phase structure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffraction peaks of the four groups of samples matched well with the standard PDF card (PDF: #54-0894). 30 Four groups of samples belong to the hexagonal system, with the P63/mmc spatial group, indicating that these samples have a P2-type layered structure (Supporting Information Figure S1). The diffraction peak of the NiO impurity phase is observed in the doped samples, which is related to the dissolution limit of nickel ions in the P2 phase structure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The atomic compositions (Ni, Mn, Mg) of the three prepared compounds were measured by ICP-AES, as listed in Table S1, and the results approach the nominal values. Diffraction peaks of the four groups of samples matched well with the standard PDF card (PDF: #54-0894) . Four groups of samples belong to the hexagonal system, with the P 63/ mmc spatial group, indicating that these samples have a P2-type layered structure (Supporting Information Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the chemical ratio plays a vital role for enlightening electrochemical performances of all the prepared materials 51,52 . Higher content of sodium (Na) increased the capacity and limited amount of Magnesium (Mg) swap improved structural stability of the NMN (Mg‐0.1) and NMN (Mg‐0.05) cathode materials 23‐26 . The substitution of Mg content increases the d‐spacing of the prepared materials with increase in concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Hou et al 23 observed that limited quantity of Mg substituted P2‐type Na 0.67 Mn 0.67 Mg 0.1 Ni 0.23 O 2 cathode material provides outstanding cycling performance and good structural stability. Besides, Mg deputized manganese based P2‐type cathode materials are sufficiently available in literature, such as P2‐Na 0.67 Ni 0.25 Mn 0.65 Mg 0.1 O 2, 24 P2‐Na 0.5 Ni 0.2 Mn 0.7 Mg 0.1 O 2 , 25 and P2‐Na 0.67 Ni 0.28 Mn 0.67 Mg 0.05 O 2 26 but Mg deputized manganese based O3‐type cathode materials are limited.…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, we need to exploit electrode materials with high energy density and excellent cycle performance. [4][5][6] In the preparation of batteries, electrode materials and electrolytes play an important role in the overall performance and practical application value of batteries. As the key electrode material, the anode material has always been the research hotspot and focus.…”
Section: Introductionmentioning
confidence: 99%